Molecular identification of tortoise beetle and its endosymbiotic bacteria - B. G. Sangeetha; Gadha Dileep; S. Lekshmi; P. Drishya; E. R. Harish (JOURNAL OF ROOT CROPS, 2023)
Tortoise beetles are one of the important defoliator pests of sweet potato, associated with a wide variety of bacterial endosymbionts that confer many ecologically relevant traits to the host insect. Endosymbiotic bacteria (ESB) play a vital role even in the physiology of the host, hence identification of ESB associated with the aphids will help to develop important strategies for the management of this noxious pest. Cassidini is the largest tribe of tortoise beetle in Kerala represented by 18 species in four genera, followed by Aspidimorphinia and notosacanthini. In the present study, molecular characterization of the sweet potato defoliator and endosymbiontic bacteria associated with them, was done. By molecular characterization they were identified as Chiridopsis sp. and sequences were deposited at NCBI with accession no OR416859. Morphological characters of the isolated revealed that each isolate has different colony characters. Further, the genomic DNA was isolated from each of the EPB isolates and PCR amplification of 16S rRNA gene was carried out using universal primers. The 16S rDNA gene sequences of endosymbiotic bacterial isolates were generated by sequencing the PCR product and were aligned with each other by using BioEDIT software. The nucleotide sequences were compared with those in the NCBI databases using the Basic Local Alignment Search and were identified as were confirmed as Kosakonia cowanii and Kosakonia sp. The 16S rRNA gene sequences were also deposited at NCBI database with accession no OR426444, OR418414. From the aligned sequences phylogenetic tree was constructed by the Neighbor- Joining method using MEGA version 11.